An S-locus independent pollen factor confers self-compatibility in 'Katy' apricot. - Elena Zuriaga (Public Library of Science (PLoS), 2013)
Loss of pollen-S function in Prunus self-compatible cultivars has been mostly associated with deletions or insertions in the S-haplotype-specific F-box (SFB) genes. However, self-compatible pollen-part mutants defective for non-S-locus factors have also been found, for instance, in the apricot (Prunus armeniaca) cv. 'Canino'. In the present study, we report the genetic and molecular analysis of another self-compatible apricot cv. termed 'Katy'. S-genotype of 'Katy' was determined as S(1)S(2) and S-RNase PCR-typing of selfing and outcrossing populations from 'Katy' showed that pollen gametes bearing either the S(1)- or the S(2)-haplotype were able to overcome self-incompatibility (SI) barriers. Sequence analyses showed no SNP or indel affecting the SFB(1) and SFB(2) alleles from 'Katy' and, moreover, no evidence of pollen-S duplication was found. As a whole, the obtained results are compatible with the hypothesis that the loss-of-function of a S-locus unlinked factor gametophytically expressed in pollen (M'-locus) leads to SI breakdown in 'Katy'. A mapping strategy based on segregation distortion loci mapped the M'-locus within an interval of 9.4 cM at the distal end of chr.3 corresponding to ∼1.29 Mb in the peach (Prunus persica) genome. Interestingly, pollen-part mutations (PPMs) causing self-compatibility (SC) in the apricot cvs. 'Canino' and 'Katy' are located within an overlapping region of ∼273 Kb in chr.3. No evidence is yet available to discern if they affect the same gene or not, but molecular markers seem to indicate that both cultivars are genetically unrelated suggesting that every PPM may have arisen independently. Further research will be necessary to reveal the precise nature of 'Katy' PPM, but fine-mapping already enables SC marker-assisted selection and paves the way for future positional cloning of the underlying gene.